Quenching-Chemiluminescence Determination of Trace Amounts of l-Tyrosine Contained in Dietary Supplement by Chemiluminescence Reaction of an Iron-Phthalocyanine Complex - Takao Ohtomo; Shukuro Igarashi; Yoshitaka Takagai; Osamu Ohno (Journal of Analytical Methods in Chemistry)
The chemiluminescence (CL) signal immediately appeared when a hydrogen peroxide solution was injected into an iron-phthalocyanine tetrasulfonic acid (Fe-PTS) aqueous solution. Moreover, the CL intensity of Fe-PTS decreased by adding L-tyrosine. Based on these results, the determination of trace amounts of L-tyrosine was developed using the quenching-chemiluminescence. The calibration curve of L-tyrosine was obtained in the concentration range of 2.0×10−7 M to 2.0×10−5 M. Moreover, the relative standard deviation (RSD) was 1.63 % (𝑛=5) for 2.0×10−6 M L-tyrosine, and its detection limits (3σ) were 1.81×10−7 M. The spike and recovery experiments for L-tyrosine were performed using a soft drink. Furthermore, the determination of L-tyrosine was applied to supplements containing various kinds of amino acids. Each satisfactory relative recovery was obtained at 98 to 102%.